Living supply chains : how to mobilize the enterprise around delivering what your customers want - Gattorna, John (Harlow, England : Pearsonl, 2006)
Living Supply Chains contains much more than its title suggests. This fine book challenges modern managers to consider again the role of supply chains in their businesses and offers genuine answers to the questions they face. John Gattorna highlights the way forward in matching supply and customer demand." Michael Andrews, Director, Tenon Ltd John Gattorna has brought Supply Chain right into the executive suite where it belongs. The opportunity for business leaders clearly outlined in Living Supply Chains is to create real organizational alignment with your end markets, and in the process better comprehend the role leadership and people play in making supply chain an integral part of a High-Performance business." Jeffrey Russell, Managing Partner, Supply Chain Asia Pacific, Accenture The challenge of supply chains has long been omnipresent, but as our world becomes more complex and our supply lines longer, the power of our supply chain management capabilities to create and destroy value is magnified. Why do our supply chains succeed or fail? The answer lies in alignment. The alignment of the needs and values of our customers, our own organisation and our suppliers. When it works it's truly magnificent, and what makes it work is people. People are at the heart of Living Supply Chains, and the key to a better supply chain future." Jon Bumstead, Strategy & Business Planning Director, DHL EXEL Supply Chain John Gattorna is one of the most original thinkers in the fast-changing arena of supply chain management. He has pioneered the idea of dynamic alignmentwhich is so powerfully presented in this ground-breaking book. If proof were needed that successful companies compete through their supply chain capability, then this fascinating book provides it." Martin Christopher, Professor of Marketing & Logistics, Cranfield School of Management, author of bestselling Logistics and Supply Chain Management "Dr Gattorna has enlivened the book with real examples from around the world both insightful and highly readable" Ralph Evans, CEO, FAICD J. Sainsbury recently lost share in the market by failing with their supply chain. Wal-mart and Dell won in the market by getting theirs right. Smart supply chains can be decisive. In the J Sainsbury debacle, there was nothing wrong with the strategy, except no one thought to check if the personnel in the company were capable of delivering such complex and sophisticated plan within such a short timeframe, and they are pay...
Bibliographic Level Mode of Issuance: Monograph
Includes bibliographical references (p. 323-326) and index.
English
Description based on print version record.
Keywords: Management; Technology and Applied Sciences Management and Auxiliary Service; General management